The Significance of Comparative Genomics in Modern Evolutionary Venomics - Drukewitz, Stephan Holger; von Reumont, Björn Marcus (Frontiers in Ecology and Evolution, 2019)
Venoms evolved convergently in diverse animal lineages as key adaptations that increase the evolu-tionary fitness of species which are manifold employed for defense, predation and competition. They constitute complex cocktails of various toxins that feature a broad range of bioactivities. The majority of described venom proteins belong to protein families that are known to comprise housekeeping genes or harbor protein-domains, which are present in genes with non-venom related functions. However, the evolutionary processes and mechanisms that foster the origin of these venom proteins and triggered their recruitment into the venom delivery system are still critically discussed. In most instances single or combined proteomic and transcriptomic approaches are applied to de-scribe venom compositions and the biological context of venoms. For neglected species these studies represent crucial contributions to improve our understanding of venom diversity on a broader scale. Nonetheless, the inference of the evolutionary origin of putative toxins in these studies could be mis-leading without appropriate coverage of gene populations from different tissue samples (gene com-pleteness) or complementary genome data. Providing a valid backbone to correctly map transcriptome and proteome data, whole genome sequences facilitate a clear distinction between variability of venom proteins or toxins due to posttranslational modifications, alternative splicing and false-positive matches that stem from sequencing or read processing and assembly errors. High-quality whole genome sequence data of venomous species are still sparse and unevenly distrib-uted within taxon lineages. However, to reveal the evolutionary pattern of putative toxins in venom-ous lineages and to identify ancestral variants of venom proteins, the appropriate sampling of ge-nomes from venomous and non-venomous species is crucial. Nevertheless, larger comparative studies based on multiple whole genome data sets are still sparse to uncover processes of venom evolution. Here, we review the general potential of comparative genomics in venomics to unravel mechanisms and patterns of evolutionary origin of toxin genes. Finally, we discuss the benefit of whole genome data to improve transcriptomics and proteomics-only studies, in particular if datasets are applied to assess the evolutionary origin of venom proteins.